Survival of metastatic gastric cancer: Significance of age, sex and race/ethnicity - Yang, Dongyun; Hendifar, Andrew; Lenz, Cosima; Togawa, Kayo; Lenz, Felicitas; Lurje, Georg; Pohl, Alexandra; Winder, Thomas; Ning, Yan; Groshen, Susan; Lenz, Heinz-Josef (Journal of Gastrointestinal Oncology; Vol 2, No 2 (June 01, 2011): Journal of Gastrointestinal Oncology, 2011)
Background: Despite the success of modern chemotherapy in the treatment of large bowel cancers, patients with metastatic gastric cancer continue to have a dismal outcome. Identifying predictive and prognostic markers is an important step to improving current treatment approaches and extending survival. Methods: Extracting data from the US NCI’s Surveillance, Epidemiology, and End Results (SEER) registries, we compared overall survival for patients with metastatic gastric cancer by gender, age, and ethnicity using Cox proportional hazards models. 13,840 patients (≥ 18 years) were identified from 1988-2004. Males and females were categorized by age grouping and ethnicity. Results: 19% of Hispanic patients were diagnosed < 45 years of age as compared to 5.5% of Caucasians. Caucasian patients and men were more likely to be diagnosed with tumors in the gastric cardia (P